Determinants of Unplanned Pregnancy in Married Women in North Sumatra Province (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Unplanned pregnancy remains a public health problem as it negatively affects fetal development and adversely impacts the mother and child’s health. In the efforts to reduce maternal dan infant mortality, as well as improve maternal health, unplanned pregnancy occurs due to several factors such as age, knowledge, contraceptive failures, and finances. The study aimed to determine the factors associated with the incidence of unwanted pregnancy. This study implemented a cross-sectional design using secondary data from the 2019 Program Performance and Accountability Survey of North Sumatra Province. The bivariate analysis was performed through a simple logistic regression. Multiple logistic regression was performed in multivariate analysis. The result showed that there were 21.3% of women reported their last pregnancy as an unplanned pregnancy. The study concluded that factors associated with an unplanned pregnancy are age at the last pregnancy, wealth at a lower index, having two or more children, and not working. Having two or more children is the most dominant factor in an unplanned pregnancy.